2018
DOI: 10.1111/tmi.13056
|View full text |Cite
|
Sign up to set email alerts
|

Village‐scale (Phase III) evaluation of the efficacy and residual activity of SumiShield®50 WG (Clothianidin 50%, w/w) for indoor spraying for the control of pyrethroid‐resistantAnopheles culicifaciesGiles in Karnataka state, India

Abstract: Indoor residual spraying with SumiShield WG was found effective, operationally feasible and safe, and it is effective for up to 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 18 publications
4
46
0
Order By: Relevance
“…Using this definition Tenebenal™ can be reported as active in this study for at least 18 months on ceramic, wood and cement tile substrates at all but the lowest concentration tested (0.025%). For some active ingredients being developed for use as IRS against mosquitoes, most notably those which are pro-insecticides, it is proposed that mortality should be scored later, due to their novel mode of action being slower acting than the pyrethroids for which the WHO guidelines were developed [ 25 , 26 ]. When applied to mud surfaces, the speed of action seemed to decrease with time post-treatment, suggestive of a dose-dependent speed of action.…”
Section: Discussionmentioning
confidence: 99%
“…Using this definition Tenebenal™ can be reported as active in this study for at least 18 months on ceramic, wood and cement tile substrates at all but the lowest concentration tested (0.025%). For some active ingredients being developed for use as IRS against mosquitoes, most notably those which are pro-insecticides, it is proposed that mortality should be scored later, due to their novel mode of action being slower acting than the pyrethroids for which the WHO guidelines were developed [ 25 , 26 ]. When applied to mud surfaces, the speed of action seemed to decrease with time post-treatment, suggestive of a dose-dependent speed of action.…”
Section: Discussionmentioning
confidence: 99%
“…The residual effects observed were driven by the insecticide used (bendiocarb residuality is expected to last between 3 and 5 months), and its interaction with treated substrates (in our case, painted walls, cloth, wood and plastic). Given the recent development of new residual insecticide formulations for malaria, which extend residual duration out to 6–8 months and are effective against pyrethroid-resistant mosquitoes [33, 34], there is potential for extending residual power of TIRS beyond the 4-month mark.…”
Section: Discussionmentioning
confidence: 99%
“…To date, phase II trials of these respective interventions have reported promising results with multiple resistant vector species [8, 10, 14, 17, 22, 26, 27]. Furthermore, a recent phase III trial in India, demonstrated greater reductions in the density of indoor, pyrethroid-resistant Anopheles culicifacies with SumiShield ® 50WG, compared to Actellic ® 300CS (pirimiphos-methyl) [28]. Prospective community-level implementation of such interventions, as part of National Malaria Control Programmes (NMCPs), is first predicated on demonstrable efficacy against local vector populations.…”
Section: Introductionmentioning
confidence: 99%